Foreign Direct Investment, Trade Openness, and Macroeconomic Outcomes: Growth and Inflation from SAARC Countries - Yadav Mani Upadhyaya; Kul Prasad Pandey (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This study explores the effects of trade openness and FDI on macroeconomic results, specifically economic growth and inflation, in the SAARC countries over the period of 1980-2023. Using unbalanced panel data for member countries, we utilized a series of econometric techniques, including fixed effects, random effects, system GMM (system generalized method) panel cointegration, and Dumitrescu-Hurlin panel Granger causality tests, in our analysis. We found that FDI and trade openness significantly enhance economic growth; specifically, one percent increase in FDI generates a growth increase of approximately 0.35% to 0.38%-point increase in GDP growth (based on System GMM estimates). Additionally, FDI and trade openness also help reduce inflation, supporting the globalization hypothesis. Evidence from the cointegration tests indicated a long-run relationship over the period, and the causality tests of all variables indicated bidirectional causality between trade and economic growth, and unidirectional effects from trade openness to GDP growth and FDI to inflation were found. We confirmed through the interaction effects that FDI stimulates economic growth more in open economies than in closed ones. The findings establish the trade and investment linkages and possible dual benefits of external integration in the SAARC countries.